Improving DoD support to FEMA's all-hazards plans - McNerney, Michael J. (Michael Joseph) (Research report (Rand Corporation), 2015)
"Disaster preparedness and response is a national priority, in which the U.S. Department of Defense (DoD) plays a supporting -- but potentially crucial -- role. In the ten years since Hurricane Katrina, the Federal Emergency Management Agency (FEMA) has taken steps to strengthen its ability to plan and coordinate the U.S. government's response to disasters, while the U.S. Department of Defense (DoD) has worked to improve its support to FEMA. This research reviews and analyzes how DoD and FEMA work together to plan and execute disaster response activities, and recommends areas for improvement. The study team (1) analyzed FEMA plans and DoD policies for Defense Support of Civil Authorities (DSCA); (2) analyzed how DoD provides DSCA support to FEMA, including key stakeholder perceptions, in order to identify potential capability gaps that DoD could fill; and (3) developed recommendations for how DoD can improve its support -- in terms of planning, coordination, and providing requested capabilities -- to FEMA"--Publisher's web site.